DEVELOPMENT AND VALIDATION OF AN INSTRUMENT TO MEASURE THE IMPLEMENTATION OF ‘PROGRAM GURU PENYAYANG’ - Nor Hasnida Che Md Ghazali; Syaza Hazwani Zaini; Norfishah Mat Rabi; Hasniza Othman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
A valid and reliable instrument is needed to assess the implementation of a program known as ‘Program Guru Penyayang’ in schools. The purpose of this study is to develop the instrument and validate it. The instrument is in the form of questionnaire distributed to a sample of 230 primary school teachers teaching Orang Asli students. The content validity is assessed by the experts and the construct validity is measured by Exploratory Factor Analysis. The reliability of the instrument is measured using internal consistence reliability, which is alpha coefficient reliability or Cronbach Alpha. Results of Exploratory Factor Analysis suggested that 23 items need to be removed due to their non-dimensionality as they have more or less equal loadings on several factors. Thus, the final draft of the instrument contains 46 items which is valid and reliable. It yielded high values of internal consistency as reflected by the Cronbach alpha values. Even though the validity and reliability of the instrument are within the acceptable range, more data need to be gathered using a bigger sample size, and further analysis using confirmatory factor analysis could be used to explore deeper into the psychometric characteristics of the items before the instrument can be finalized.